(3HGdYQHjI hGdEfLdjRjIs - (3eMehO eMeO Ydj(B, (3UHQgs ((3GdbGgQI(B:s (3OGQ GdcJH GdbGfhfjI(B,s, 2002)
(3JfGhd gPG GdcJGH GdeHGOF hGdbhGYO GdCSGSjI GdJi JMce GdUjGZI GdbGfhfjI , HTcd YGe, hGdUjGZI GdJTQjYjI, HTcd NGU(B. (3hjQej Edi JMbjb gOa Pi Tbjf, GdChd GdJYQa Ydi GdeHGOF hGdbhGYO GdSdjeI GdeQYjI HGdaYd ai GdUjGZI GdbGfhfjI hJCUd gPg GdeHGOF hGdbhGYO hGdKGfi(B: (3HMK GdYjhH GdJi JThH GdUjGZI GdbGfhfjI heMGhdI GdNQhL HHYV GdJhUjGJ hGdMdhd GdJi ef TCfgG JHSjW GdhKGFb GdbGfhfjI hLYdgG ef GdhVhM HMjK jSgd agegG djS aMSH ef LGfH OQGSi GdbGfhf hEfeG CjVG ef LGfH GdbGQF GdYGOj(B. (3hJHQR CgejI OQGSI GdUjGZI GdJTQjYjI HGddZJjf GdYQHjI hGdEfLdjRjI, HTcd NGU , ai VhA GdGJLGg GdOhdi dJhMjO GdbhGfjf ai eNJda CfMGA GdYGde hhVY GdGJaGbjGJ GdOhdjI GdedReI, hGdGJLGg Edi GdYhdeI(B. (3hbO JQJH Ydi cd Pdc, Cf CUHMJ cd Ohd dG JSJWjY Cf JSf bhGfjfgG HeYRd Yf GdbhGfjf hGdGJaGbjGJ GdOhdjI hai JfGhdfG dehVhY GdcJGH, GbJUQfG Ydi HMK CUhd GdUjGZI GdbGfhfjI, HhLg YGe, hGdUjGZI GdJTQjYjI, HhLg NGU, dCSHGH YOI ChdkG(B: (3Cf GdUjGZI GdJTQjYjI JYO Cge CfhGY GdcJGHGJ GdbGfhfjI, agi GdJi JMOO GdMbhb, hJaQV GdhGLHGJ hGdGdJRGeGJ, hJMXQ Ydi GdeNGWHjf HgG GdbjGe HCYeGd eYjfi, hJNdhge SdWI JbOjQjI hUdGMjGJ hGeJjGRGJ(B. (3KGfjG(B: (3Gf eaghe GdUjGZI GdJTQjYjI dG jbJUQ , HeYfGg GdhGSY ceG SfhVM ajeG HYO, Ydi UjGZI GdJTQjYGJ aMSH, Hd jeJO djTed ed GdhKGFb GdbGfhfjI GdJi JfXe GdYdGbGJ hJMOO GdMbhb hGdGdJRGeGJ(B. (3hef Ke, jONd ai EWGQ eUWdM GdUjGZI GdJTQjYjI, HGdEVGaI Edi GdJTQjYGJ, GdYbhO hGdGJaGbjGJ hGdbhGYO hGddhGFM, hZjQgG(B. (3KGdKG(B: (3Ef eLGd GdcJGH GdbGfhfjI gh ef GdQMGHI HMK dG jecf JfGhdg ai cJGH hGMO(B.s
Keywords: (3GdJTQjYGJ GdbGfhfjIs; (3GdUjGZI GdbGfhfjIs